Sex, Sexism and bullying - Carretero Bermejo, Raúl (Revista Complutense de Educación, 2011)
This research approaches the study of the relationship, first between sex and sexism, and then between these two variables and bullying. This study could show that boys are more involved in bullying situations more because of their sexist beliefs than for the biological fact of to be a boy.
Keywords: Sexism; Hostile Sexism; Benevolent Sexism; Violence; Sex; Bullying.